KETERAMPILAN PSIKOLOGIS MODEL BK âPROAKTIFâ-R UNTUK MENINGKATKAN REGULASI EMOSI GURU SD - , RURI FITRIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study is to examine The Psychological Skills of âPROAKTIFâ-R Guidance and Counselling Model to Improve The Regulation of emotion in The Teachers of Elementary School Teachers. The hypothesis of this study is there is a The Psychological Skills of âPROAKTIFâ-R Guidance and Counselling Model effectively improving emotion regulation of elementary school teachers. There is also a significant difference in the emotional regulation score between experimental and control groups. Emotion regulation of elementary school teachers should influence how teachers express positive emotions, manage stress, and interact with others. The subjects of this study were 32 Muhammadiyah elementary school teachers in Sleman. The design of this experiment was untreated pretest-posttest control group design. A measure of emotional regulation was developed by using aspects from thompsonâs emotion regulation indicators (1994). The training module was modifying module The âPROAKTIFâ model of psychological skill from Atamimi (2011). Data were analysed using anava mix design. The result of this study shows that The Psychological Skills of âPROAKTIFâ-R Guidance and Counselling Model improving emotion regulation. There is a difference in emotion regulation score between experimental and control groups (F = 12.171, P<0.05). The results of this study confirmed the hypothesis.